The effect of nail characteristics on surface bacterial counts of surgical personnel before and after scrubbing. Issue 7 (28th June 2017) - Hardy, Jade M.; Owen, Tina J.; Martinez, Steven A.; Jones, Lisa P.; Davis, Margaret A.
Abstract: Objective: To determine the influence of nail characteristics on bacterial counts on the fingers of surgery personnel. Study design: Randomized nonblinded controlled crossover study design. Sample population: Veterinary students, small animal surgery technicians, small animal surgery interns/residents, and small animal surgery faculty in a veterinary teaching hospital (n = 21). Methods: Subjects were randomized into one of 2 groups; group 1 wore nail polish (P) for 1 week and group 2 (control) had nonpolished (NP) fingernails. Each subject changed groups the following week. Fingernail lengths were measured each day and fingernail samples were collected before and after presurgical scrub and after surgery. Total bacterial counts (TBC) and suspected staphylococci were counted on blood agar media and mannitol salt agar. The association between bacterial counts and nail biting, position of the volunteer, duration of the surgery, whether the nail polish was chipped, duration of nail polish application, type of surgery, and handedness was tested. Log‐transformed CFU counts were compared with a Student's t test and presence or absence of bacteria were compared using Fisher's exact test. Results: TBC, quantities of staphylococci, other gram‐positive organisms, and gram‐negative bacilli did not differ between P and NP personnel. The only variable associated with higher bacterial counts consisted of nail lengths greater than 2 mm. Conclusion: Nail polish did not influence bacterial counts and types of isolates, but nail length is a risk factor for increased bacterial counts. Based on our results, we recommend that nail length be kept under 2 mm.